2019
DOI: 10.1002/adhm.201900001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating CAR‐T Cell Therapy in a Hypoxic 3D Tumor Model

Abstract: Despite its revolutionary success in hematological malignancies, chimeric antigen receptor (CAR) T cell therapy faces disappointing clinical results in solid tumors. The poor efficacy has been partially attributed to the lack of understanding in how CAR-T cells function in a solid tumor microenvironment. Hypoxia plays a critical role in cancer progression and immune editing, which potentially results in solid tumors escaping immunosurveillance and CAR-T cell-mediated cytotoxicity. Mechanistic studies of CAR-T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 101 publications
1
75
1
Order By: Relevance
“…[14][15][16][17][18] However, they are labor-intensive and difficult to use. [14][15][16][17][18] However, they are labor-intensive and difficult to use.…”
Section: However Current Tools For Evaluating Car-t Functions Lack Smentioning
confidence: 99%
“…[14][15][16][17][18] However, they are labor-intensive and difficult to use. [14][15][16][17][18] However, they are labor-intensive and difficult to use.…”
Section: However Current Tools For Evaluating Car-t Functions Lack Smentioning
confidence: 99%
“…The results showed that NK-92 cells modified by CAR can directly target the ubiquitous epithelial antigen (EpCAM), which can be effectively targeted in multiple organoids [118]. Another group explored the drug sensitivity and cytotoxicity of CAR-T cells by establishing different oxygen gradients in the 3D model of ovarian cancer [119]. The results showed that the OC 3D model can study CAR-T cytotoxicity better than the 2D model.…”
Section: Application Of Immunotherapymentioning
confidence: 99%
“…Similarly, a 3D microfluidic human ovarian cancer model was developed by embedding human epidermal growth factor receptor 2 (HER2) + ovarian cancer cells (SKOV3) in a micropatterned gelatin methacryloyl (GelMA) hydrogel and micromilled hypoxia device to establish an oxygen gradient across micropatterned cancer cells. [ 161 ] It consisted of perfusion channels for the delivery of HER2‐targeting 4D5 scFv CAR‐T cells and to study the infiltration as well as the cytotoxicity of CAR‐T cells under heterogeneous oxygen concentration conditions within the tumor. The enhanced cytotoxic activity of CAR‐T cells was observed under the physiologically relevant oxygen level, whereas immunosuppression was increased under the hypoxic condition as shown by increased PD‐L1 expression by the tumor cells under hypoxia culture.…”
Section: Other Relevant Immunocompetent Ooc Modelsmentioning
confidence: 99%